Pengaruh Kinerja Keuangan terhadap Pertumbuhan Laba Pada Perusahaan BUMN Sektor Pertambangan yang Terdaftar di BEI - Muhammad Irfai Sohilauw; Wahyuni Wahyuni; Muhammad Akob Kadir (Business Management Journal, 2022)
An increase in company profits reflects the company's good performance, and vice versa, the decrease in company profits reflects the company's performance that has not been maximized. Therefore, the ups and downs of a company's profit growth can be understood through financial ratio analysis. In this case, financial performance is represented by the Current Ratio (CR), Debt to Equity Ratio (DER) and Return On Investment (ROI). The objectives of this research are to: (1) determine the effect of the Current Ratio on profit growth in state-owned mining companies listed on the IDX. (2) Knowing the effect of the Debt to Equity Ratio on profit growth in state-owned mining companies listed on the IDX. (3) Knowing the effect of Return On Investment on profit growth in state-owned mining companies listed on the IDX. The sampling technique used is saturated sampling, with a total sample of 3 state-owned mining companies listed on the Indonesia Stock Exchange for the period 2011-2020. The analytical method used in this research is multiple regression analysis. The results of the research show that the Current Ratio (CR) has a positive and irrelevant impact on profit growth ((0.261 < 1.98861) and (0.795 > 0.05)). Debt to Equity Ratio (DER) has a negative and relevant impact on profit growth ((-2.486 < 1.98861) and (0.015 < 0.05)). Meanwhile, Return On Investment (ROI) has a positive and relevant impact on profit growth (2.883 > 1.98861) and (0.005 > 0.05).